Biodiesel From Waste Palm Oil and Chicken Fats as an Alternative Fuel for Diesel Engine - Abu Saleh, Ahmed; E., Taharah; R., Rahman; S., Hamdan; H.H., Masjuki (ENCON 2013, 2013)
Biodiesel, fatty acid methyl ester (FAME) is a biodegradable, renewable and sustainable energy. It is derived from vegetable oil or animal fats through transesterification process with short chain alcohols or by the esterification of fatty acids. The transesterification reaction consists of transforming triglycerides into FAMEs, in the presence of an alcohol and a catalyst, with glycerol as a by-product. Waste oil and fats have emerged as one of the most promising feedstock for biodiesel production due to its availability and inexpensive price as compared to other sources of biodiesel production. In addition, the usage of waste oil and fats for biodiesel production also helps in reducing the disposal problems which give adverse effect to the environment. This research was conducted to study the conversion of waste oil and fats into biodiesel, engine performance and exhaust emission analysis of diesel engine using the wastage biodiesel blends. The conversion of biodiesel from chicken fats was higher than that of waste cooking oil. The highest yield was found to be 96% at oil-to-methanol ratio of 1:4 and 0.5 wt% of potassium hydroxide (KOH). Biodiesel blends with petroleum diesel ranging from B0 (100% petroleum diesel) to B50 (50% v/v biodiesel + 50% v/v petroleum diesel) were prepared to carry out the diesel engine performance test. The results showed the brake power and specific fuel consumption (SFC) were increased as biodiesel percentages increased in fuel blends. The engine power output of biodiesel blends were lower than petroleum diesel and decreased as biodiesel percentage increased in fuel blends. The exhaust emission tests showed that biodiesel blends had a slightly lower emission of carbon monoxide (CO), nitrogen oxide (NOx) and hydrocarbon (HC) than petroleum diesel.